AIDS and ‘building a wall’ around Christian country in rural Papua New Guinea - Dundon, Alison (The Australian journal of anthropology, 2010)
This paper explores an ongoing dialogue about Christianity in light of the recent influx of HIV and AIDS into the villages of the Gogodala of Western Province, Papua New Guinea. I argue that a suggestion by a woman in late 2004 to ‘build a wall’ around the Gogodala region in Western Province in order to stop or slow the spread of HIV/AIDS reflects a recent concern with the sustainability of this rural Christian community, referred to in English as ‘Christian country’. Understanding AIDS to be a threat posed largely from outsiders, whether Papua New Guinean or European, sections of these primarily village-based communities aim to create both a physical and metaphorical boundary between themselves and outsiders. At present, local prevention and intervention strategies concerning HIV and AIDS focus on conservative, evangelical narratives about the preservation of the principles and practices of Christian country, through the repudiation of unrestrained sexuality, for example, which is believed to be increasingly prevalent not only in their own area but throughout urban Papua New Guinea. A growing divide between rural and urban Gogodala, then, has become a major part of the local dialogue about AIDS and represents significant contestation over the practices and ideational basis of Christian country.